Professional identity and role transitions in clinical managers. Issue 3 (18th May 2015) - Spehar, Ivan; Frich, Jan C; Kjekshus, Lars Erik
Abstract : Purpose: – The purpose of this paper is to investigate how clinicians' professional background influences their transition into the managerial role and identity as clinical managers. Design/methodology/approach: – The authors interviewed and observed 30 clinicians in managerial positions in Norwegian hospitals. Findings: – A central finding was that doctors experienced difficulties in reconciling the role as health professional with the role as manager. They maintained a health professional identity and reported to find meaning and satisfaction from clinical work. Doctors also emphasized clinical work as a way of gaining legitimacy and respect from medical colleagues. Nurses recounted a faster and more positive transition into the manager role, and were more fully engaged in the managerial aspects of the role. Practical implications: – The authors advance that health care organizations need to focus on role, identity and need satisfaction when recruiting and developing clinicians to become clinical managers. Originality/value: – The study suggests that the inclusion of aspects from identity and need satisfaction literature expands on and enriches the study of clinical managers.